The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/adhm.202000043
|View full text |Cite
|
Sign up to set email alerts
|

Complement Receptor Targeted Liposomes Encapsulating the Liver X Receptor Agonist GW3965 Accumulate in and Stabilize Atherosclerotic Plaques

Abstract: Atherosclerosis is characterized by the retention of lipids in foam cells in the arterial intima. The liver X receptor (LXR) agonist GW3965 is a promising therapeutic compound, since it induces reverse cholesterol transport in foam cells. However, hepatic LXR activation increases plasma and liver lipid levels, inhibiting its clinical development. Herein, a formulation that specifically enhances GW3965 deposition in the atherosclerotic lesion is aimed to be developed. GW3965 is encapsulated in liposomes functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…[45] A similar biodistribution and macrophage association was observed in a study by Benne and coworkers, who showed increased retention of cyclic peptide Lyp-1 liposomes in atherosclerotic plaque macrophages. [51] Taken together, our results corroborate the accumulation of IV-administered constructs in atherosclerotic plaques, specifically in macrophages, and highlight the potential of Dextran-TPP mitochondria for treatment in other diseases characterized by both metabolic dysregulation and enhanced vascular permeability/preferential site-specific localization.…”
Section: Dextran-tpp Mitochondria Accumulated In Atherosclerotic Plaq...supporting
confidence: 80%
“…[45] A similar biodistribution and macrophage association was observed in a study by Benne and coworkers, who showed increased retention of cyclic peptide Lyp-1 liposomes in atherosclerotic plaque macrophages. [51] Taken together, our results corroborate the accumulation of IV-administered constructs in atherosclerotic plaques, specifically in macrophages, and highlight the potential of Dextran-TPP mitochondria for treatment in other diseases characterized by both metabolic dysregulation and enhanced vascular permeability/preferential site-specific localization.…”
Section: Dextran-tpp Mitochondria Accumulated In Atherosclerotic Plaq...supporting
confidence: 80%
“… 104,105 In recent years, delivery of anti-atherosclerosis drugs using liposomes has also attracted widespread attention. 16,106–108 Considering that curcumin can reduce the side effects of statins, Li et al designed liposomes loaded with atorvastatin and curcumin (AC-Lipo) for combination therapy of atherosclerosis. They found that, compared to liposomes loaded with only atorvastatin, AC-Lipo significantly reduced the expression of ICAM-1 and E-selectin on plaque endothelial cells, leading to decreased atherosclerotic plaque content, showing AC-Lipo could synergistically reduce plaque lipid content and inflammatory cytokine expression.…”
Section: Organic Nps For Atherosclerosis Treatmentmentioning
confidence: 99%
“…In general, NPs applied for anti-atherosclerosis purposes may be divided primarily into inorganic NPs and organic NPs. Compared to inorganic NPs, organic NPs, such as polymeric NPs, 14 liposomes, 15 micelles, 16 and high-density lipoprotein NPs, 17 have the advantages of high drug-loading capacity, good biocompatibility, long circulation time, and rapid elimination from the body. Organic NPs are modified to optimize their target specificity, tissue-penetration depth, duration, and so on, providing the possibility for early diagnosis and effective treatment of atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“… 253 LyP-1 liposomes loaded by GW3965 also locate to atherosclerotic plaques and cut down the number of macrophages. 254 …”
Section: Strategies Of Lesion-localizing Delivery For Treating Athero...mentioning
confidence: 99%